Size-resolved fungal bioaerosol diversity over an Indian agricultural field and their ecosystem-health implications - Varghese, Emil; Krishnamoorthy, Sarayu; Hredhya, T. K.; Kumari, Kiran; Bhattacharya, B. K.; Kundu, S. S.; Goswami, Jonali; Yadav, Shweta; Verma, Rama Shanker; Ravikrishna, R.; Gunthe, Sachin S. (Frontiers in Microbiology, 2025)
Particle size is one of the important characteristics of bioaerosols that influences their fate and transport. This study investigates the characterization and size-resolved fungal bioaerosol diversity at an agricultural field in northern India during the winter season. The size-resolved bioaerosol samples were collected using a Micro-Orifice Uniform Deposition Impactor (MOUDI) in two phases: the onset of winter (phase 1) and the end of winter (phase 2), and Next-Generation Sequencing (NGS) was used to identify bioaerosol diversity up to the species level. Ascomycota was the predominant phylum in both phases, with Aspergillus penicillioides being the dominant species in phase 1 and Mycosphaerella tassiana in phase 2. The size range 1–1.8 μm exhibited higher diversity (H =3.7 and 2.0 in phases 1 and 2, respectively) and evenness (Eh = 0.9 and 0.5 in phases 1 and 2, respectively), while the 5.6–10 μm range has the highest dominance (D = 0.4 and 0.5 in phases 1 and 2, respectively). A total of 189 Operational Taxonomic Units (OTUs) were identified in phase 1 and 128 OTUs in phase 2, classified into ‘pathogenic’ and ‘beneficial/useful’ categories to study their role in ecosystem-health interactions. Species such as Aspergillus flavus, Aspergillus niger, Macrophomina phaseolina, and Penicillium citrinum were identified as affecting multiple crop hosts, highlighting the potential for multiple crop yield loss. The size range 1–8-3.2 μm had the highest number of species in phase 1, while 3.2–5.6 and 5.6–10 μm were predominant in phase 2 for plant pathogens. The 1.8–3.2 μm range also had the highest number of potential human pathogens in both phases. This study is the first to explain fungal bioaerosol diversity in an agricultural field based on size and its role in ecosystem-health interaction. These findings emphasize the importance of monitoring and managing fungal bioaerosols to protect agricultural productivity and human health.